Sexual rhetoric in the works of Joss Whedon new essays - Waggoner, Erin B. 1983- (McFarland, 2010)
"Topics covered include the role of virginity, lesbianism and homoeroticism in the shows and the comics, the nature of masculinity and femininity and gender stereotypes, an exploration of sexual binaries, and a ranking of the Buffy characters on the Kinsey scale of sexuality. Together these essays constitute a much-needed addition to the expanding body of Whedon gender scholarship"--Provided by publisher